A survey paper on blockchain as a service platforms. (3rd February 2022) - Alshurafa, Samer Muneer; Eleyan, Derar; Eleyan, Amna
Blockchain provides more security and decentralised systems. However, it is difficult for startups and small companies to build and deploy their blockchain networks. So, cloud computing providers make it easy for those to work with blockchain using their networks and cloud infrastructure through using blockchain as a service platform. There are many blockchain as a service providers and platforms. This survey provides an overview of 23 blockchain-as-a-service platforms and provides a comparison based on provider, blockchain protocol, blockchain type, cost, security, and support of smart contract.